Wayward creatures - Lorentz, Dayna (Clarion Books, 2021)
Twelve-year-old Gabe is in emotional turmoil after feeling the effects of his parents' money woes and seeing his best friends begin to hang out with other kids on their soccer team. When he finally gets the chance to hang out with his friends again, he hopes to impress them by shooting off fireworks that he steals from a local store. When the fireworks ignite, they cause a fire in the woods near his house and damage several acres of land. Gabe is blamed for the fire and must help clean up the mess he caused through a court order. While working in the ravaged fields, Gabe encounters a coyote named Rill, who also is going through his own difficulties with his family, but now is injured from the fire and can't return to them. As he works in the area, Gabe realizes the consequences of his actions, dedicating himself to helping Rill recover, and in the process discovering a new friend.